Metaprofiling of the bacterial community in sorghum silages inoculated with lactic acid bacteria - Puntillo, Melisa (2022)
To characterize the fermentation process and bacterial diversity of sorghum silage inoculated with Lactiplantibacillus plantarum LpAv, Pediococcus pentosaceus PpM and Lacticaseibacillus paracasei LcAv.